ANALISIS RESTRUKTURISASI BIROKRASI DALAM PENGEMBANGAN GOOD GOVERNANCE PADA SEKERTARIAT DAERAH KABUPATEN KONAWE UTARA - Bakti Bakti; La Ode Muhammad Elwan (Journal Publicuho, 2018)
The problem of this research is : (1) How to restructure of bureaucracy supports good governance at the secretary of local government North konawe regency.  (2) How to restructure of bureaucracy that implemented by secretary of local government north konawe regency creates good governance.The aim of this research is : (1) To analyze how to restructure  of bureaucracy at the secretary of local government north konawe regency supports good governance. (2) To know how to restructure that carried out by the secretary of local government north konawe regency in supporting good governance.This research is a study case, the population of this research is all head of a division , at secretary of local government north konawe regency and taking totally sampling, data is collected by interview, observation, and documentation to all respondents and inform men . data is processed by descriptive qualitative.The result of the research shows that (1) Implementation of restructuring of bureaucracy in supporting good governance at the secretary of local government north konawe regency has generally been carried out and met their needs to organization dynamic. (2) Implementation of restructuring of bureaucracy toward good governance at the secretary of local government north konawe regency.Based on the result of research can be concluded that restructure of bureaucracy at the secretary of local government north konawe regency has been better carried out,  because of all resources potency has been optimally maximized.  Keywords: Bureaucratic restructuring, Good Governance